THE IMPROVEMENT OF ANAEROBIC WASTEWATER TREATMENT WITH STRUCTURED MEDIA GROWTH SYSTEM - Darwati, Ir; Hastuti, Elis (MATTER: International Journal of Science and Technology, 2017)
The anaerobic domestic wastewater treatment plant at communal scaleare seen not be sustainable and the process s to be improve by anaerobic and aerobic process - structured media growth system, in regard with still high water source quality degradation and water reuse development.This paper aims to research the improvement of communal wastewater treatment system through anaerobic –aerobic of structured media growth system which had applied in some urban areas. The treatment system applied the anaerobic baffled reactor (ABR),submerged media growth system and rotating biological contactor system has low area requirement and has to concern optimization energy. The treatment system applied the hybrid upflow anaerobic sludge blanket - submerged media growth system and hybrid sub surface of constructed wetland has low cost operation and maintanence Both of the system have many advantages and could consider as improvement of the anaerobic communal wastewater treatment plant. The evaluation of performance these systems show the treated water an meet effluent standard and can be reused as non potable source in urban areas.